Does context matter? The gendered impact of study conditions on dropout intentions from higher education - Marczuk, Anna; Strauss, Susanne (Zeitschrift für Erziehungswissenschaft, 2023)
This paper aims to understand how study conditions impact men and women’s dropout intentions differently. As a first step, we analyse the gendered impact of three aspects of study conditions that were at the centre of the Bologna Process: achievement norms, the structure of the curriculum and practical components in the study programme. As a second step, we aim to understand how individual-level differences between men and women (performance, academic self-efficacy and perceived psychological burdens) mediate this gendered impact of study conditions on dropout intentions. We use the German Student Survey data (2000–2016), which allows for valid measurement of study conditions at the subject group level. Our results show that women’s dropout intentions tend to increase in study contexts with high achievement norms, while men benefit more than women from highly structured study contexts. The practical component, in turn, lowers the dropout intentions of both groups equally.